Fabricating authenticity in Soviet Hungary : the afterlife of the First Hungarian Soviet Republic in the age of state socialism - Apor, Péter (Anthem Press, 2013)
This book explores the memory of the First Hungarian Soviet Republic of 1919, which proved crucial for communist Hungarian political culture in the twentieth century. Apor approaches the topic in an innovative way, focusing on the understudied aspects of European memory cultures. Offering great insights on how a dictatorship remembers and the concept of authenticity, Apor's study integrates the broad range of processes through which history is sought to be rendered authentic. The volume successfully reveals the crooked history of the retrospective revisions of the iconic First Republic between the years of its 30th and 40th anniversary, 1949 and 1959.